El liberalismo económico y la crisis - De Vroey, Michel (Lecturas de Economía, 2009)
<!--[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} p.MsoListParagraph, li.MsoListParagraph, div.MsoListParagraph {mso-style-priority:34; mso-style-unhide:no; mso-style-qformat:yes; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:36.0pt; mso-add-space:auto; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} p.MsoListParagraphCxSpFirst, li.MsoListParagraphCxSpFirst, div.MsoListParagraphCxSpFirst {mso-style-priority:34; mso-style-unhide:no; mso-style-qformat:yes; mso-style-type:export-only; margin-top:0cm; margin-right:0cm; margin-bottom:0cm; margin-left:36.0pt; margin-bottom:.0001pt; mso-add-space:auto; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} p.MsoListParagraphCxSpMiddle, li.MsoListParagraphCxSpMiddle, div.MsoListParagraphCxSpMiddle {mso-style-priority:34; mso-style-unhide:no; mso-style-qformat:yes; mso-style-type:export-only; margin-top:0cm; margin-right:0cm; margin-bottom:0cm; margin-left:36.0pt; margin-bottom:.0001pt; mso-add-space:auto; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} p.MsoListParagraphCxSpLast, li.MsoListParagraphCxSpLast, div.MsoListParagraphCxSpLast {mso-style-priority:34; mso-style-unhide:no; mso-style-qformat:yes; mso-style-type:export-only; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:36.0pt; mso-add-space:auto; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;} @page Section1 {size:612.1pt 792.1pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> En los numerosos debates que evocan el liberalismo económico, éste se presenta como una realidad monolítica; el objetivo de este artículo consiste en poner de manifiesto que distintos grados de liberalismo deben distinguirse: el pleno liberalismo, el liberalismo mitigado y el antiliberalismo mitigado, con subdistinciones al interior de las dos primeras categorías. En la primera parte se recuerdan las características que marcan el liberalismo económico en general. En la segunda se menciona la justificación que Adam Smith ha dado del liberalismo. Finalmente, en la tercera parte, inicio el trabajo de des-homogenización del liberalismo económico y muestro cómo distintas formas de éste se han encadenado históricamente, en particular, respecto a las grandes crisis económicas. Palabras clave: Smith, liberalismo, tipos de liberalismo, economía de mercado, crisis. Clasificación JEL: A11, B10, N00. Abstract: In the many debates concerning economic liberalism, this appears as a monolithic reality. The aim of this paper is to show that this is not the case and that different degrees of liberalism must be distinguished: total liberalism, mitigated liberalism and mitigated anti-liberalism, with subdistinctions within the first two categories. In the first part of the paper, the characteristics of economic liberalism overall are recalled. Subsequently, Adam Smith's justification of liberalism is introduced. Finally, in the third part, I attempt to des-homogenize economic liberalism and show how different forms of this have been linked historically, particularly with respect to the great economic crises.Abstract: In the many debates concerning economic liberalism, this appears as a monolithic reality. The aim of this paper is to show that this is not the case and that different degrees of liberalism must be distinguished: total liberalism, mitigated liberalism and mitigated anti-liberalism, with subdistinctions within the first two categories. In the first part of the paper, the characteristics of economic liberalism overall are recalled. Subsequently, Adam Smith's justification of liberalism is introduced. Finally, in the third part, I attempt to des-homogenize economic liberalism and show how different forms of this have been linked historically, particularly with respect to the great economic crises. Keywords: Smith, liberalism, types of liberalism, market economy, crisis. Classification JEL: A11, B10, N00. Résumé: Dans les nombreux débats évoquant le libéralisme économique, celui-ci est présenté comme une réalité monolithique. L'objectif de cet article est de montrer que ceci n'est pas le cas et que différents degrés de libéralisme doivent être distingués : le plein libéralisme, le libéralisme mitigé et l'anti-libéralisme mitigé, avec des sous-distinctions au niveau des deux premières catégories. Dans sa première partie, les traits saillants du libéralisme économique en général sont rappelés. Dans la seconde, j'évoque la justification qu'Adam Smith en a donnée. Enfin, dans la troisième partie, j'entreprends le travail de dés-homogénéisation du libéralisme économique et montre comment différentes formes de celui-ci se sont enchaînées historiquement, notamment en réaction aux grandes crises économiques. Mots clé: Smith, libéralisme, types de libéralisme, économie de marché, crises. Clasification JEL : A11, B10, N00.